A study on factors influencing brand loyalty among consumers in Malaysian consmetic industry / Murni Izzati Kamarudzaman - Kamarudzaman, Murni Izzati (Faculty of Business and Management, 2015)
It is the objective for all companies to gain long-term profitability from their businesses. This could be achieved by establishing long-term relationship with the consumers. In order to do so, it is vital to attain consumers’ loyalty. Making sure consumers are loyal is a constant battle. Marketers need to carefully lay out strategies to ensure every aspect of their businesses are able to attract consumers. Thus, this quantitative research is aimed towards proving the correlation between factors such as product quality, price, promotion and brand image with brand loyalty. This study is also aimed towards identifying the most influential factor in determining consumers’ brand loyalty. Data has been collected from occupants of Plaza Mont Kiara. 135 respondents were selected through convenient sampling. Questionnaire was used as the instrument to collet responses. From the analysis conducted, result has proven that there was a significant correlation between product quality, price and brand image with brand loyalty. Besides that, product quality was identified as the strongest factor influencing brand loyalty through the multiple regression analysis conducted. From the findings, researcher has come up with some recommendations to help brands and marketer to come out with innovative strategies in attracting more loyal consumers. Firstly, they should put more priority in improving the quality of their products so that they fit to various skin types. They should also produce best-value-for-money products. Lastly, brands and marketers could instil ethical business approach to increase the attractiveness of their brands.